Ethnic differences in the consistency and accuracy of perceived exertion - Sweatt, Sarah Katherine (Am J Hum Biol, 2015)
OBJECTIVES: This study investigated the effect of weight loss and weight regain on accuracy of perceived exertion (APE) in previously overweight African American (AA) and European American (EA) women. METHODS: Formerly overweight women (n=102, age 20–44 yrs) completed a weight loss program to achieve BMI <25kg/m(2). Physiological variable of exertion and rating of perceived exertion (RPE, Borg’s 6–20 Scale) were recorded during submaximal aerobic exercise prior to, immediately following, and approximately one year after weight loss. APE was defined as the composite score of physiological variables (heart rate, ventilation rate, and respiratory exchange ratio) minus RPE. RESULTS: APE was significantly different from the composite score of physiological variables at baseline and at 1-year follow-up for EA women (0.347±0.88 p<0.05 and 0.53±0.92, p<0.01 respectively) and at 1-year follow-up for AA (−0.37±1.1, p<.01). EA women had lower physiological effort at baseline and 1-year follow-up states (−0.24±0.66 p<0.05; and, −0.27±0.84 p<0.05 respectively). AA women had higher physiological effort, at 1-year follow-up state (0.21±0.61, p<0.01). CONCLUSIONS: Physiologic effort and perceived exertion contributed independently to the racial differences in APE, and APE may be an important trait to evaluate before planning an exercise intervention.